MODERN PROBLEMS OF THE INFLUENCE OF ENTERPRISES PRODUCING POLYMER PRODUCTS ON HUMAN HEALTH AND THE ENVIRONMENT (Literature review) (World Bulletin of Public Health, 2024)
Today, the increasing demand for polymer products not only in our country but also worldwide, as well as developing and improving ways to reduce the impact of harmful chemical substances in their composition on human health and the environment, remains one of the pressing issues facing specialists in the field of preventive medicine. The article examines the experiences of foreign countries focused on the problems of various factors affecting human health and the environment in the production of polymer products.